Transcriptomic analysis using RNA sequencing and phenotypic analysis of Salmonella enterica after acid exposure for different time durations using adaptive laboratory evolution - Ghoshal, Mrinalini; Bechtel, Tyler D.; Gibbons, John G.; McLandsborough, Lynne (Frontiers in Microbiology, 2024)
Introduction: This study serves as the final part of a two-part series that delves into the molecular mechanisms driving adaptive laboratory evolution (ALE) of Salmonella enterica in acid stress. The phenotypic and transcriptomic alterations in the acid evolved lineages (EL) of Salmonella enterica serovar Enteritidis after 70 days of acid stress exposure have been analyzed. Materials and Methods: The stability of phenotypic changes observed after 70 days in acetic acid is explored after stress removal using a newly developed evolutionary lineage EL5. Additionally, the impact of short-term acid stress on the previously adapted lineage EL4 is examined. Results: The results indicate that the elevated antibiotic minimum inhibitory concentration (MIC) observed after exposure to acetic acid for 70 days was lost when acid stress was removed. This phenomenon was observed against the human antibiotics, meropenem, ciprofloxacin, gentamicin, and streptomycin. The MIC of meropenem in EL4 on day 70 was 0.094 mM but, removal of acetic acid stress after day 70 caused the MIC to reduce to 0.032 mM. However, a swift regain of the elevated MIC is observed after stress reintroduction, and within 4 days the MIC returned to 0.094 mM. After 20 more days of adaptation in acetic acid, the meropenem MIC increased to 0.125 mM. Similar trends were observed with the other human antibiotics tested. The MIC of acetic acid in EL4 on day 70 was observed to be 35 mM which remained constant even after removal of acetic acid stress. Readaptation of EL4 in acetic acid for 20 more days caused the acetic acid MIC to increase to 37 mM. Bacterial whole genome sequencing of EL5 revealed base substitutions in several genes involved in pathogenesis such as the phoQ gene and wzc gene. Transcriptomic analysis of EL5 revealed upregulation of virulence, drug resistance, toxin-antitoxin, and iron metabolism genes. Unstable Salmonella small colony variants (SSCV) of S. Enteritidis were also observed in EL5 as compared to the wild-type unevolved S. Enteritidis. Discussion: This study presents a comprehensive understanding of the evolution of phenotypic, genomic, and transcriptomic changes in S. Enteritidis due to prolonged acid exposure through ALE.